Using the Health Belief Model to Predict Vaccination Intention Among COVID-19 Unvaccinated People in Thai Communities - Seangpraw, Katekaew; Pothisa, Tharadon; Boonyathee, Sorawit; Ong-Artborirak, Parichat; Tonchoy, Prakasit; Kantow, Supakan; Auttama, Nisarat; Choowanthanapakorn, Monchanok (Frontiers in Medicine, 2022)
Background: The coronavirus disease 20-19 (COVID-19) pandemic has become one of the biggest challenges to individual health and the public health system worldwide. COVID-19 morbidity and mortality are increasing, impacting almost every country including Thailand. This study used the Health Belief Model (HBM) as a framework to examine the intention of unvaccinated people living in northern Thailand to receive COVID-19 vaccines. Methods: This cross-sectional study was conducted during October and November 2021. A total of 1,024 participants who are currently living in four northern provinces of Thailand, Chiang Mai, Chiang Rai, Lamphun, and Phayao, were recruited to participate in the study. The questionnaire was developed using an HBM structure to obtain information about the perceived severity, perceived susceptibility, self-efficacy, perceived benefits and barriers, cues to action, and preventive behaviors relating to COVID-19 vaccination and the decision to become vaccinated. Multiple linear regression was used to analyze the data. Results: The unvaccinated participants were an average of 44.45 ± 16.63 years of age and more than half were women (54.5%). The COVID-19 preventive behavior score used perceived severity (B=0.26), self-efficacy (B=0.51), perceived benefits and barriers (B=0.11), and cues to action (B=0.18) after adjusting for age, underlying disease, and body mass index (R2=42.5%). The COVID-19 vaccination decision score was positively correlated with perceived severity (B=0.13), perceived susceptibility (B=0.25), perceived benefits and barriers (B=0.21), and cues to action (B=0.27) after adjusting for underlying disease (R2=38.7%). Discussion: The results demonstrated the usefulness of using the HBM structure to understand individual intention to receive a COVID-19 vaccine. Communities should consider a COVID-19 health campaign and programs that use the HBM model as a framework for altering perceptions and beliefs about the COVID-19 vaccine and improving vaccination rates among unvaccinated people in rural northern Thailand.